Simulative Study of Simple Ring Resonator Based Brewster Plate for Power System operation Stability - Iraj Sadegh Amiri; Ahmed Nabih Zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This study has outlined the simulative study of simple ring resonator based Brewster plate in the air. The obtained results are achieved with the variations of space length, curvature radius and phase angle of the spherical mirror. Beam radius criterion and stability parameters are measured with the variations of refractive index and thickness of Brewster plate in the air. The negative and positive effects of increasing operating parameters are observed on the performance of ring resonator system efficiency.